INVESTIGATING ENGLISH TEACHERS' DIGITAL LITERACY: CURRENT USE OF TECHNOLOGY IN CLASSROOM AND PROFESSIONAL DEVELOPMENT OF DIGITAL LITERACY - Ali Sudin, - (2022)
Menyadari pesatnya kemajuan teknologi dan implikasinya terhadap pendidikan, semua pendidik maupun siswa wajib untuk terus meningkatkan literasi digitalnya. Dengan demikian penelitian ini bertujuan untuk mendapatkan informasi dari guru Bahasa Inggris Indonesia mengenai literasi digital mereka, integrasi teknologi guru dalam praktik kelas, dan pengembangan profesional guru dalam meningkatkan literasi digital mereka. Penelitian ini menggunakan penelitian kualitatif dan keseluruhan responden yang terlibat dalam penelitian ini adalah 20 guru bahasa Inggris dari beberapa sekolah menengah atas. Studi ini mengungkapkan bahwa semua guru telah mencapai beberapa kegiatan yang mencerminkan literasi digital yang memadai berdasarkan standar TESOL. Namun mereka masih kurang dalam menggunakan alat-alat teknologi yang lebih canggih di kelas mereka. Mereka menyatakan bahwa mereka harus lebih meningkatkan literasi digital mereka dengan mengikuti beberapa program pengembangan professional untuk menciptakan TELL yang lebih efektif. Program efektif yang disarankan oleh guru antara lain peer-teacher, pelatihan, dan forum online. In recognition of the rapid advancements in technology and their implications for education, all educators as well as students are obligated to continuously upgrade their digital literacy. Thus this study is aimed to gain information from Indonesian English teachers regarding their digital literacy, the teachers' integration of technology in classroom, and the teacher professional development in increasing their digital literacy. This study employed a qualitative research and the overall respondents involved in this study were 20 English teachers from several senior high schools in Sumedang. The study revealed that all the teachers have achieved several activities which reflect their adequate digital literacy based on TESOL standard. However they are still lacking in using more sophisticated technology tools in their classes. They stated that they have to improve more their digital literacy by joining some teacher professional development programs to create more effective TELL. The effective programs suggested by the teachers including peer-teachers, training, and online forum.